Графічна неоднорідність прозового тексту: структурно-композиційний і стилістичний прийом (на матеріалі роману Марії Матіос «Солодка Даруся») - Бибик, Світлана; Bybyk, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті запропоновано аналіз прозових мікроконтекстів з елементами графічної неоднорідності. Диференційовано формально-синтаксичні, структурно-семантичні та структурно-композиційні засоби графічної неоднорідності, їхню роль у формуванні оповіді, організації сюжету твору та його композиції. Гру графічними образами кваліфіковано як стилістичний прийом в оповідній структурі творів доби постмодернізму. The article offers an analysis of prose microcontext with graphic elements of heterogeneity. The formal syntactic, structural and semantic, structural and compositional heterogeneity of graphical tools are differentiated in one of the novels of Maria Matios, underline their role in the formation of the narrative, the story works organization and its composition. The game graphic images are qualified as a stylistic device in the narrative structure of postmodern works. The peculiarity of the use of capital letters in the selection of the author's modality. n this regard, analyzed microcontext where graphic heterogeneity of contributes to the alignment of certain stylistic evaluation, psychological emphasis in the process of unfolding storyline and alignment of the text composition, providing the basic idea of the work.
The Graphical Heterogeneity of the Text Prose Work: Structural and Compositional and Stylistic Device (Based on the Novel by Mariа Matios «Sweet Darusya»)
Keywords: оповідність; авторська модальність; стилістичний прийом; графічна неоднорідність тексту; графічна стилістика тексту; narrative; the author's modality; a stylistic device; graphic heterogeneity of of the text; graphic style of the text